2019
DOI: 10.3390/ijerph16061051
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heart Rate Variability Biofeedback Training on Mental Health of Pregnant and Non-Pregnant Women: A Randomized Controlled Trial

Abstract: In this study, we examined the efficacy of heart rate variability (HRV)-biofeedback on stress and stress-related mental health problems in women. Furthermore, we examined whether the efficacy differed between pregnant and non-pregnant women. Fifty women (20 pregnant, 30 non-pregnant; mean age 31.6, SD = 5.9) were randomized into an intervention (n = 29) or a waitlist condition (n = 21). All participants completed questionnaires on stress, anxiety, depressive symptoms, sleep, and psychological well-being on thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Only one study was rated as low risk of bias [49], six studies were rated as moderate risk of bias [40][41][42][43][44]50]; nine studies were rated as high risk of bias [38,39,41,42,47,48,[51][52][53]. The most common sources of bias related to blinding; selective reporting bias in most studies was unclear as few studies were pre-registered or had published protocols.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study was rated as low risk of bias [49], six studies were rated as moderate risk of bias [40][41][42][43][44]50]; nine studies were rated as high risk of bias [38,39,41,42,47,48,[51][52][53]. The most common sources of bias related to blinding; selective reporting bias in most studies was unclear as few studies were pre-registered or had published protocols.…”
Section: Study Qualitymentioning
confidence: 99%
“…Characteristics of the included studies are summarised in Table 1. Seven studies [40,42,[44][45][46][47][48] examined effects of prenatal interventions for women at risk of developing stress, anxiety and/or depression [45,48], or who already experienced elevated levels [40,42,44,46,47]. One study examined effects of an intervention for low-income pregnant women who were, for the most part, unmarried [41].…”
Section: Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several preliminary studies have reported a therapeutic benefit of HRV-B for patients with high levels of anxiety, stress, and depression 27,[30][31][32][33] . Thus, clinicians have begun integrating HRV-B into existing depressive treatments 34 .…”
Section: Introductionmentioning
confidence: 99%